2005
DOI: 10.1111/j.1365-2929.2004.02058.x
|View full text |Cite
|
Sign up to set email alerts
|

Teaching and learning population and preventive health: challenges for modern medical curricula

Abstract: These findings have important implications for modern medical curricula. The challenge in teaching population health issues is to balance students' needs to understand and apply the principles of population and preventive health and the biopsychosocial model of patient care, with the need for them to be confident they will be able to practise safely if they do so.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 30 publications
(41 reference statements)
0
22
0
1
Order By: Relevance
“…It was reported that students might be afraid that focusing on population health issues could compromise their ability to practise acute medicine (Rêgo & Dick 2005). The qualitative data of the current study indicated that our students' attitudes towards community health issues were not negative overall.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…It was reported that students might be afraid that focusing on population health issues could compromise their ability to practise acute medicine (Rêgo & Dick 2005). The qualitative data of the current study indicated that our students' attitudes towards community health issues were not negative overall.…”
Section: Discussionmentioning
confidence: 50%
“…Woodward reported that undergraduate medical students are primarily interested in the diagnosis and treatment of individual cases; population-based health care is seldom regarded as important (Woodward 1994;Rêgo & Dick 2005). It was reported that students might be afraid that focusing on population health issues could compromise their ability to practise acute medicine (Rêgo & Dick 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Medical students have reported poor role modelling of public health skills (Rego & Dick 2005). Focus groups with medical students in Canada found that the lack of exposure to practising public health specialist role models was a major factor in students' disengagement with the public health curriculum (Tyler et al 2009).…”
Section: Interactive Deliverymentioning
confidence: 99%
“…Using a range of activities ensures the teaching appeals to students with different learning styles, for example: brainstorming and role-play to appeal to activists, knowledge quizzes and background references for theorists, small group discussion and links to videos for reflectors, and case studies and problem-solving for pragmatists (Vaugh & Baker 2001). Whilst all these methods help the tutor to organise the session, the most important skill is to maintain an encouraging atmosphere for sharing ideas.Teaching should include exposure to public health specialist role models 4.Medical students have reported poor role modelling of public health skills (Rego & Dick 2005). Focus groups with medical students in Canada found that the lack of exposure to practising public health specialist role models was a major factor in students' disengagement with the public health curriculum (Tyler et al 2009).…”
mentioning
confidence: 99%